2012
DOI: 10.1111/j.1447-0756.2011.01770.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of a 22q11 deletion in a second‐trimester fetus with conotruncal anomaly, absent thymus and meningomyelocele: Kousseff syndrome

Abstract: A 30-year-old nulliparous woman was seen for a detailed ultrasound scan at 20 weeks of gestation. The scan revealed a male fetus with truncus arteriosus, membranous ventricular septal defect, absent thymus and sacral meningomyelocele. A 46,XY karyotype with a 22q11 deletion was detected. The parents chose to terminate the pregnancy. The pathological autopsy showed normal facial structures, minimal ventricular dilatation in the brain and a sacral meningomyelocele. Overlapping toes and a left claw-hand were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…The variable expression of the 22q11.2 deletion and a low threshold for clinical testing has resulted in its association in case reports or small case series with myriad other findings (e.g. fetal megalourethra, split‐hand/foot malformation, congenital diaphragmatic hernia, umbilical or inguinal hernia, tracheoesophageal fistula/esophageal atresia/laryngeal atresia, polydactyly, craniosynostosis, and neurological abnormalities like neural tube defects and arhinencephaly) . Increased nuchal translucency, polyhydramnios, and intrauterine growth restriction may be consequences of the 22q11.2 deletion and/or of associated congenital anomalies .…”
Section: Epidemiology and Prevalence Of 22q112 Deletions In Prenatalmentioning
confidence: 99%
See 1 more Smart Citation
“…The variable expression of the 22q11.2 deletion and a low threshold for clinical testing has resulted in its association in case reports or small case series with myriad other findings (e.g. fetal megalourethra, split‐hand/foot malformation, congenital diaphragmatic hernia, umbilical or inguinal hernia, tracheoesophageal fistula/esophageal atresia/laryngeal atresia, polydactyly, craniosynostosis, and neurological abnormalities like neural tube defects and arhinencephaly) . Increased nuchal translucency, polyhydramnios, and intrauterine growth restriction may be consequences of the 22q11.2 deletion and/or of associated congenital anomalies .…”
Section: Epidemiology and Prevalence Of 22q112 Deletions In Prenatalmentioning
confidence: 99%
“…fetal megalourethra, split-hand/foot malformation, congenital diaphragmatic hernia, umbilical or inguinal hernia, tracheoesophageal fistula/esophageal atresia/laryngeal atresia, polydactyly, craniosynostosis, and neurological abnormalities like neural tube defects and arhinencephaly). 12,[26][27][28][29] Increased nuchal translucency, polyhydramnios, and intrauterine growth restriction may be consequences of the 22q11.2 deletion and/ or of associated congenital anomalies. 12,24,[30][31][32] One recent study reported dilation of the cavum septum pellucidum in 67.5% of second trimester fetuses with 22q11.2 deletions.…”
Section: Epidemiology and Prevalence Of 22q112 Deletions In Prenatalmentioning
confidence: 99%
“…Subsequently in 2002, the third child previously reported by Kousseff [1984] was found to have a deletion on 22q11 by FISH [Forrester et al, ]. A few other reports of myelomeningocele in individuals with 22q11.2DS have been reported in detail in the medical literature [Toriello et al, ; Palacios et al, ; Nickel et al, ; Nickel and Magenis, ; Seller et al, ; Maclean et al, ; Kinoshita et al, ; Canda et al, ; McDonald‐McGinn et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…A 2q35-36.2 deletion containing the PAX3 gene has been reported in patients with NTD 18,42 . A 22q11.2 deletion syndrome has also been reported, but the link to NTD is unclear 19,43 . Similarly, a SOX duplication (Xq27.1) has been diagnosed in a few patients with myelomeningocele 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal abnormalities have been reported in 2.6-16.3% of fetuses or newborns with NTDs, with the most common being trisomy 13, trisomy 18 and triploidy [12][13][14][15][16][17] . Some microdeletions and microduplications have also been reported to be associated with NTDs [18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%